تقييم الخصائص الشكلية والوظيفية والأثر العمراني لأشجار شارع الكورنيش الغربي في مدينة اللاذقية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The research dealt with the analysis of tree rows and study the diversity of trees and appreciate their idealism and study the relationship of trees with engineering elements in the West Corniche Street in Latakia City. Results of this paper revealed prominent breaks in the arboreal rows, and that these rows contain four botanic species(Phonenix dactylifera L.,Ficus nitid L.,Melia azedarachL. , Washingtonia filifera H.), which served to furnish the street with monotonic beauty and humility in botanic diversity. Findings showed an ideal decrease in the value of the used botanic species where (Ficus nitid L., Washingtonia filifera H., Phonenix dactylifera L. ) attained a mark of /7.26,7.13,7.11/ respectively, while the degree of the( Melia azedarachL.) was acceptable (7.62/ degree) out of 10 degrees. the results showed that the dimensions between trees and service elements were   appropriate, and the shadows caused by the trees at 12 noon are spaced spots due to the gaps,. The shadows formed at 17 o'clock are observed to cover a relatively large area of The asphalt section of the street . تناول البحث تحليل الصفوف الشجرية ودراسة تنوع الأشجار وتقدير مثاليتها ودراسة علاقة الأشجار مع العناصر الهندسية في شارع الكورنيش الغربي في مدينة اللاذقية . أظهرت نتائج البحث وجود تقطعات بارزة في الصفوف الشجرية للشارع.كما بيَّنت أن الصفوف الشجرية في شارع الكورنيش الغربي  تحتوي على أربعة أنواع شجرية وهي نخيل تمر الزينةPhonenix dactylifera L. والتين اللامعFicus nitid L.والازدرخت . Melia azedarach Lونخيل الواشنطونيا filifera H. Washingtonia , مما سبب تشوهاً لجمالية الشارع وتواضعاً في الغنى النباتي لهذه الصفوف . كما كشفت نتائج البحث عن تدني القيمة لدرجة مثالية التين اللامع ونخيل الواشنطونيا ونخيل تمر الزينة /7.26,7.13,7.11/  على التوالي في حين كانت درجة الازدرخت مقبولة /7.62/ درجة من أصل /10/ درجات. كما أظهرت النتائج بأن الأبعاد بين الأشجار والعناصر الخدمية كانت مناسبة, وأن الظلال المتشكلة عن وجود الأشجار في الساعة 12ظهراً عبارة عن بقع متباعدة بسبب الفجوات, أما الظلال المتشكلة في الساعة 17 فيلاحظ بأنها تغطي مساحة كبيرة نسبياً من القسم الإسفلتي للشارع.